2018
DOI: 10.1097/xeb.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

A new improved graphical and quantitative method for detecting bias in meta-analysis

Abstract: Detection of publication and related biases remains suboptimal and threatens the validity and interpretation of meta-analytical findings. When bias is present, it usually differentially affects small and large studies manifesting as an association between precision and effect size and therefore visual asymmetry of conventional funnel plots. This asymmetry can be quantified and Egger's regression is, by far, the most widely used statistical measure for quantifying funnel plot asymmetry. However, concerns have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
524
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 600 publications
(529 citation statements)
references
References 31 publications
2
524
0
3
Order By: Relevance
“…Heterogeneity was assessed using the I 2 statistic, with values ≥75% indicating considerable heterogeneity . Reporting bias across studies (eg publication bias) was examined visually using “funnel plots” and the more sensitive “Doi plots” and formally using the Luis Furuya‐Kanamori (LFK) index, to see if the prevalence rates changed with increasing sample size. In the funnel plots and Doi plots, a higher prevalence is displayed by a higher “Double Arcsin Prevalence”, and a higher standard error indicates a lower sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was assessed using the I 2 statistic, with values ≥75% indicating considerable heterogeneity . Reporting bias across studies (eg publication bias) was examined visually using “funnel plots” and the more sensitive “Doi plots” and formally using the Luis Furuya‐Kanamori (LFK) index, to see if the prevalence rates changed with increasing sample size. In the funnel plots and Doi plots, a higher prevalence is displayed by a higher “Double Arcsin Prevalence”, and a higher standard error indicates a lower sample size.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the risk of publication bias by visually examining Doi plots and assessing the Luis Furuya‐Kanamori (LFK) index, rather than funnel plots . Funnel plots perform poorly when the effect size is a prevalence proportion .…”
Section: Methodsmentioning
confidence: 99%
“…Funnel plots perform poorly when the effect size is a prevalence proportion . The LFK index outperformed Egger's regression for detection of asymmetry because of biases caused by selective publication . The Doi plot uses a folded variant of the normal quantile‐ versus ‐effect plot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that bias occurs when studies are selected into strata such that systematic differences between larger and smaller studies emerge (where none initially existed), as shown in the funnel or Doi plot (Figures 2e4 in our published article [2]). The association develops solely because of selection of studies into a quality stratum and does not imply that all the results within strata defined by quality ranking are biased, and this is a situation akin to publication bias [3,4]. Page et al next state that within stratum bias would only be the case if results in smaller studies were biased and less precise.…”
Section: Letter To the Editormentioning
confidence: 99%